2020
DOI: 10.1186/s12864-020-07124-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tissue transcriptome analysis using hybrid-sequencing reveals potential genes and biological pathways associated with azadirachtin A biosynthesis in neem (azadirachta indica)

Abstract: Background Azadirachtin A is a triterpenoid from neem tree exhibiting excellent activities against over 600 insect species in agriculture. The production of azadirachtin A depends on extraction from neem tissues, which is not an eco-friendly and sustainable process. The low yield and discontinuous supply of azadirachtin A impedes further applications. The biosynthetic pathway of azadirachtin A is still unknown and is the focus of our study. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 72 publications
(85 reference statements)
0
17
0
Order By: Relevance
“…Azadirachtin is a triterpenoid compound of neem tree, which has effective insecticidal activities against a wide range of insect species, but has very low toxicity to mammals. Terpene synthase (TPS), cytochrome P450 (CYP450), alcohol dehydrogenase (ADH), acyltransferase (ACT), and esterase (EST) were proposed to be involved in biosynthesis of azadirachtin ( Wang et al, 2020 ). In this study, a large number of genes encoding CYP 450s (78), TPSs (58), and ACTs (34) were identified in secondary metabolite biosynthesis gene clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Azadirachtin is a triterpenoid compound of neem tree, which has effective insecticidal activities against a wide range of insect species, but has very low toxicity to mammals. Terpene synthase (TPS), cytochrome P450 (CYP450), alcohol dehydrogenase (ADH), acyltransferase (ACT), and esterase (EST) were proposed to be involved in biosynthesis of azadirachtin ( Wang et al, 2020 ). In this study, a large number of genes encoding CYP 450s (78), TPSs (58), and ACTs (34) were identified in secondary metabolite biosynthesis gene clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Azadirachtin is a triterpenoid compound of neem tree, which has effective insecticidal activities against a wide range of insect species, but has very low toxicity to mammals. Terpene synthase (TPS), cytochrome P450 (CYP450), alcohol dehydrogenase (ADH), acyltransferase (ACT), and esterase (EST) were proposed to be involved in biosynthesis of azadirachtin (Wang et al, 2020). In this study, a large number of genes encoding CYP P450s (78), TPSs (58), and ACTs (34) were identified in secondary metabolite biosynthesis gene clusters.…”
Section: Secondary Metabolite Analysismentioning
confidence: 96%
“…Molecular docking was performed with Autodock 4.0. Four triterpenoids (azadirone, nimbin, nimbolide, and tirucalla-7,24-dien-3β-ol) were selected as potential substrates for CYPs (Wang et al, 2020).…”
Section: Molecular Docking Analysismentioning
confidence: 99%
See 2 more Smart Citations